Vaginal microecological imbalance and expression of serum inflammatory factors in pregnant women with group B streptococcus infection and pregnancy outcome: Effect of group B streptococcus infection in pregnant women - Zhang, Wenjia; Wan, Yafang; Zhang, Yu; Xu, Lanlan; Li, Tian; Liao, Pu (Cellular and Molecular Biology, 2023)
The objective of this study was to explore the correlation between vaginal microecological imbalance and the expression of related inflammatory factors in pregnant women with group B streptococcus (GBS) infection and pregnancy outcomes. For this purpose, 100 GBS-positive pregnant women were recruited as the experimental group, and 100 GBS-negative pregnant women were recruited as the controls. The balance of vaginal microecology of pregnant women in different groups was compared. Results showed that the probability of vaginal microecological imbalance in the experimental group was much higher than against the controls. Fasting venous blood was drawn from the pregnant women in two groups. After centrifugation, the expression levels of interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), and interleukin-1β (IL-1β) in serum were detected. It was found that the expression levels of IL-6, IL-1β, and TNF-α in the experimental group were higher than against the controls. After delivery, it suggested that the incidence of premature delivery, neonatal infection, premature rupture of membranes, and other adverse childbirth in the experimental group was much higher in contrast to the controls, up to 87%. In conclusion, GBS infection can increase the incidence of vaginal microecological imbalance and the expression of serum inflammatory factors in pregnant women, and it can greatly raise the incidence of adverse pregnancy outcomes.